Impact of COVID-19 on employment: sociodemographic, medical, psychiatric and neuropsychological correlates - Thompson, Madison; Ferrando, Stephen J.; Dornbush, Rhea; Lynch, Sean; Shahar, Sivan; Klepacz, Lidia; Smiley, Abbas (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Given the nature of the persistent physical and neuropsychiatric symptoms reported in the literature, among individuals after acute COVID illness; there is growing concern about the functional implications of the Post-Acute Sequelae of COVID-19 (PASC). We aim to evaluate associations of sociodemographic, medical, psychiatric and neuropsychological factors with employment status post COVID-19. Methods: 59 participants were administered a neuropsychiatric assessment and queried about employment status and occupational difficulties months after quarantine. Two levels of comparison were conducted: 1) Those who took time off work (TTO) to those with no time off (NTO); 2) Those who reported occupational performance suffered (PS) to those who did not (PDNS). Results: TTO vs. NTO exhibited extensive differences across medical, psychiatric and neurocognitive domains. PS vs. PDNS differed on subjective measures of physical and cognitive symptoms, but not on objective testing. Conclusion: Individuals who took time off beyond COVID-19 quarantine experience persistent physical, psychiatric, subjective and objective neurocognitive burden. In contrast, occupational impairment appears to reflect subjective complaints, but not objective measures. Clinical implications are discussed.